OCCUPATIONAL CONTACT DERMATITIS - Krishnan, Saravanan; Ketut Darmada, I Gusti; Mas Rusyati, Luh Made (Bali Journal of Medical and Health Sciences, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 O cc up a t i on a l c onta c t d e r m a t i t i s is one of the most c om m on wo r k- r e lat e d i l lness e s in ma n y d e v e loped c ountr i e s, a cc ount i ng for up to o n e th i rd of a ll o cc u p a t i on a l dise a s e s . A h i g h p re v a le n c e h a s b e e n d o c ument e d in spe c ific o c c up a t i on a l g r oups, such a s c onstru c t i on wo r k e rs, nurs e s, h a i rd re s s e rs, food p r o ce ss i n g w o rk e rs a nd met a l wo r k e rs. I r ritant c onta c t d e rm a t i t i s a nd a l l e r g ic c onta c t d e r m a t i t i s a re k nown a s the two t y p e of o cc up a t i on a l c onta c t d e rm a t i t is . R e dd e ning o f skin, bl i ste r , i tc hiness a re s y mp t oms o f these d e r m a t i t is . Kno w le d g e of the f a c t o r s whi c h p re dispose to o c c up a t i on a l c onta c t d e r ma t i t i s is use f ul i n o cc up a t i on a l h ea l t h p ra c t i c e for the a ppl i ca t i on of p re v e nt i ve me a su r e s a nd for ca r ee r g uida n c e for w o rk e rs in hi g h risk o cc up a t i ons. Thus to maintain a n ef fec t i ve wo r k flow a nd g ood h ea l t h status of the wo r k e rs both the c ompa n y a nd the wo r k e rs should c onsid e r manipulating the risk f ac tors a nd t r y to d e c re a se or p r e v e nt t h e o cc up a t i on a l c ont a c t d e rm a t i t i s f r om g e t t ing w o r st. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}